Comment on “Measurement and correction of transverse chromatic offsets for multi-wavelength retinal microscopy in the living eye” - Artal, Pablo (Optical Society of America, 2012)
An interesting method to measure and correct chromatic magnification offsets in a multi-wavelength retinal imaging microscope was recently reported [Harmening et al., Biomed. Opt. Express 3, 2066 (2012)]. These values were in part related to the ocular transverse chromatic aberration (TCA). This method could be potentially used in the future to overcome the fundamental limitation to estimate the eye’s TCA with ophthalmoscopic (double-pass) configurations.